Wear-resistant anticorrosive paint and preparation method thereof

By using an abrasion-resistant anticorrosion coating containing resin emulsion, composite wear-resistant filler and pigment filler on power transmission and transformation equipment, the problem of insufficient wear resistance and environmental protection of existing coatings in harsh environments is solved, and a higher level of wear resistance and environmental protection is achieved The wear resistance and environmental protection performance extend the life of the equipment and reduce environmental pollution.

CN119286373APending Publication Date: 2025-01-10STATE GRID GANSU ELECTRIC POWER CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411320688.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The anti-corrosion coatings of existing power transmission and transformation equipment have decreased wear resistance and aging resistance in harsh environments, and there are environmental pollution problems in solvent-based coatings.

Method used

Using a wear-resistant anti-corrosion coating, including resin emulsion, composite wear-resistant filler, pigment filler, film forming agent and auxiliary agent, through specific ratios and preparation methods, a paint film with high elasticity and wear resistance is formed to reduce volatility. Emissions of organic matter.

Benefits of technology

It improves the wear resistance and environmental protection of the coating, extends the service life of the equipment, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286373A_ABST
    Figure CN119286373A_ABST
Patent Text Reader

Abstract

The invention provides a wear-resistant anticorrosive coating and a preparation method thereof. The wear-resistant anticorrosive paint comprises the following raw materials in parts by weight: raw materials of a component A and raw materials of a component B, wherein the component A comprises the following raw materials in parts by weight: 35-55 parts of resin emulsion, 8-26 parts of composite wear-resistant filler, 8-15 parts of pigment filler, 2-5 parts of film-forming agent and 1.5-3 parts of auxiliary agent; the component B comprises the following raw materials in parts by weight: 70 parts of aliphatic isocyanate tripolymer and 30 parts of propylene glycol diacetate. A paint film coated with the wear-resistant anticorrosive paint has certain elasticity and good wear resistance, scratches on the surface of the paint film are reduced, the wear-resistant protection performance is improved, and compared with an anticorrosive coating of power equipment in service, the paint has the advantages that the content of volatile organic compounds is low, the emission is low, and the environmental protection performance of the paint is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion of power transmission and transformation equipment, and specifically provides a wear-resistant anti-corrosion coating and a preparation method thereof. Background Art

[0002] In order to improve the anti-corrosion reliability of power transmission and transformation system equipment and ensure the safe and stable operation of the power network, the shells and components of the power transmission and transformation equipment are usually coated for protection.

[0003] At present, transformers, reactors, GIS, substation cabinets and other equipment in power transmission and transformation mostly use solvent-based organic coatings. Organic coatings play an important role in the corrosion protection and equipment reliability of power transmission and transformation equipment, such as using epoxy zinc-rich primer, epoxy micaceous iron intermediate paint, acrylic polyurethane topcoat, etc. for protective treatment.

[0004] However, in harsh environments such as strong winds and sand, high temperature differences, strong sunlight, and even saline-alkali land, the wear resistance and aging resistance of the coating on power transmission and transformation equipment drop sharply. In addition, the current solvent-based protective coating system releases a large amount of volatile organic compounds during the coating process, which can easily lead to environmental pollution problems. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of poor wear resistance and environmental protection performance of anti-corrosion coatings on existing power equipment.

[0006] The purpose of the present invention is to adopt the following technical solutions to achieve:

[0007] The invention provides a wear-resistant and anti-corrosion coating, which comprises, by weight: raw materials of component A: 35-55 parts of resin emulsion, 8-26 parts of composite wear-resistant filler, 8-15 parts of pigment filler, 2-5 parts of film-forming agent and 1.5-3 parts of auxiliary agent; and raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

[0008] Preferably, the resin emulsion includes at least one of a high-functionality polyurethane resin, a fluorocarbon resin and a polyhydroxy acrylic resin.

[0009] Preferably, the composite wear-resistant filler includes at least one of ultrafine ceramic microspheres, alumina, silicon carbide, polytetrafluoroethylene wax powder and zirconium oxide.

[0010] Preferably, the pigment and filler include at least one of titanium dioxide, attapulgite, precipitated barium sulfate, ultrafine wollastonite and ultrafine talc.

[0011] Preferably, the film-forming agent includes at least one of alcohol ester dodecanedione, propylene glycol butyl ether, AMP-95, dipropylene glycol butyl ether and diethylene glycol dimethyl ether.

[0012] Preferably, the auxiliary agent includes 0.5 to 1.2 parts of a defoaming agent, 0.5 to 1.2 parts of a dispersant, 0.1 to 0.8 parts of an anti-scratch agent, 0.1 to 0.8 parts of a wetting agent, and 0.3 to 1 parts of a thickener.

[0013] Preferably, the dispersant comprises at least one of a polymer containing a high-efficiency pigment adsorption group and a surfactant, a sodium salt of a maleic acid copolymer, and an acrylic acid block polymer.

[0014] Preferably, the defoaming agent includes at least one of polyether siloxane copolymer emulsion, polyether modified silicone containing silicon dioxide and polymer composite mineral oil.

[0015] Preferably, the anti-scratch agent comprises a modified hydroxyl-functional polydimethylsiloxane solution, the wetting agent comprises an organosilicon gemini structure surfactant, and the thickener comprises an alkali-swellable acrylic resin.

[0016] Based on the same inventive concept, the present invention also provides a method for preparing the wear-resistant and anti-corrosion coating, comprising: the preparation steps of component A: prefabricated slurry: by weight, add 8 to 16 parts of deionized water to the first container in sequence, add 0.5 to 1.2 parts of dispersant, 0.5 to 1.2 parts of defoamer, and 2 to 5 parts of film-forming agent in sequence on a disperser at a speed of 300 to 500 rpm, and stir and disperse for 5 to 8 minutes; add 8 to 15 parts of color filler, stir and disperse for 3 to 5 minutes; add 8 to 26 parts of composite wear-resistant filler, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of a grinder at a speed of 3000 rpm, and grind for 2 to 3 hours to obtain a prefabricated slurry; prepare a viscous liquid: add 35 to 55 parts of resin emulsion to the second container, and grind at 3000 rpm for 2 to 3 hours to obtain a prefabricated slurry. The prefabricated slurry is added to the disperser at a speed of 300 rpm, and the speed of the disperser is adjusted to 500-800 rpm. The mixture is stirred and dispersed for 3-5 minutes. 0.1-0.8 parts of an anti-scratch agent, 0.1-0.8 parts of a wetting agent and 0.3-1 parts of a thickener are added, and the viscosity of the mixed liquid is adjusted to between 75 and 85 KU to obtain a viscous liquid. Purification treatment: impurities in the viscous liquid are removed by filtering with a 100-mesh silk bag to obtain the component A. Preparation steps of the component B: by weight, 70 parts of an aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to a third container, and the two are stirred and dispersed uniformly to obtain the component B. By weight, the component A and the component B are mixed uniformly at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The wear-resistant and anti-corrosion coating of the present invention comprises raw materials of component A and raw materials of component B. Among them, the raw materials of component A include: 35-55 parts of resin emulsion, 8-26 parts of composite wear-resistant filler, 8-15 parts of pigment filler, 2-5 parts of film former and 1.5-3 parts of auxiliary agent; the raw materials of component B include: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate. The paint film of the wear-resistant and anti-corrosion coating of the present invention after coating has certain elasticity and good wear resistance, reduces scratches on the surface of the paint film, and improves the wear-resistant protective performance. Compared with the anti-corrosion coating of the current power equipment, the wear-resistant and anti-corrosion coating of the present invention has less volatile organic matter content and low emissions, which improves the environmental protection performance of the wear-resistant and anti-corrosion coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a graph showing the wear resistance test results of Example 1 of the wear-resistant and anti-corrosion coating of the present invention;

[0020] Figure 2 This is a graph showing the wear resistance test results of Example 2 of the wear-resistant and anti-corrosion coating of the present invention;

[0021] Figure 3 This is a graph showing the wear resistance test results of Example 3 of the wear-resistant and anti-corrosion coating of the present invention;

[0022] Figure 4 This is a graph showing the wear resistance test results of Example 4 of the wear-resistant and anti-corrosion coating of the present invention;

[0023] Figure 5 This is a graph showing the wear resistance test results of Example 5 of the wear-resistant and anti-corrosion coating of the present invention;

[0024] Figure 6 This is a graph showing the wear resistance test results of a comparative example of the wear-resistant and anti-corrosion coating of the present invention. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred solution of the present invention is described below in conjunction with the best embodiment of a specific application. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0026] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0027] Embodiment 1:

[0028] The embodiment of the present invention provides a wear-resistant and anti-corrosion coating, which comprises, by weight:

[0029] Raw materials of component A: 50 parts of resin emulsion, 20 parts of composite wear-resistant filler, 10 parts of pigment filler, 3 parts of film-forming agent and auxiliary agents; the auxiliary agents include 0.8 parts of defoaming agent, 0.5 parts of dispersant, 0.8 parts of anti-scratch agent, 0.4 parts of wetting agent and 0.5 parts of thickener.

[0030] Raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

[0031] The preparation method of the wear-resistant and anti-corrosion coating comprises:

[0032] 1) Preparation steps of component A:

[0033] Prefabricated slurry: add 15.2 parts of deionized water to the first container in parts by weight, add 0.5 parts of dispersant, 0.8 parts of defoamer and 3 parts of film-forming agent in a disperser at 300 rpm, and stir and disperse for 5 minutes; add 10 parts of pigment and filler, stir and disperse for 3 minutes; add 20 parts of composite wear-resistant filler, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of a grinder at 3000 rpm, and grind for 2 hours to obtain a prefabricated slurry;

[0034] Preparation of viscous liquid: Add 50 parts of resin emulsion to the second container, add the prefabricated slurry on the disperser at a speed of 300 rpm, adjust the disperser speed to 600 rpm, stir and disperse for 5 minutes, add 0.8 parts of anti-scratch agent, 0.4 parts of wetting agent and 0.5 parts of thickener, and adjust the viscosity of the mixed liquid to between 75 and 85 KU to obtain a viscous liquid;

[0035] Purification treatment: Filter with a 100-mesh silk bag to remove impurities in the viscous liquid to obtain component A, and package and seal component A for later use.

[0036] 2) Preparation steps of component B:

[0037] In parts by weight, 70 parts of aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to the third container, and the two are stirred and dispersed uniformly to obtain component B;

[0038] 3) By weight, component A and component B are mixed evenly at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

[0039] Among them, the composite wear-resistant filler includes 8 parts of ultrafine ceramic microspheres, 8 parts of silicon carbide, and 4 parts of polytetrafluoroethylene wax powder; the resin emulsion adopts high-functionality polyurethane resin; the color filler adopts 9.5 parts of titanium dioxide and 0.5 parts of attapulgite; the film-forming agent adopts 1 part of alcohol ester and 2 parts of propylene glycol butyl ether; the dispersant adopts polymers and surfactants containing high-efficiency pigment adsorption groups; the defoaming agent adopts polyether modified silicone containing silicon dioxide; the anti-scratch agent adopts modified hydroxyl-functional polydimethylsiloxane solution; the wetting agent adopts silicone twin structure surfactant; and the thickener adopts alkali-swellable acrylic resin.

[0040] Embodiment 2:

[0041] The embodiment of the present invention provides a wear-resistant and anti-corrosion coating, which comprises, by weight:

[0042] Raw materials of component A: 35 parts of resin emulsion, 8 parts of composite wear-resistant filler, 15 parts of pigment filler, 2 parts of film-forming agent and auxiliary agents; the auxiliary agents include 0.5 parts of defoaming agent, 1.2 parts of dispersant, 0.2 parts of anti-scratch agent, 0.3 parts of wetting agent and 0.5 parts of thickener.

[0043] Raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

[0044] The preparation method of the wear-resistant and anti-corrosion coating comprises:

[0045] 1) Preparation steps of component A:

[0046] Prefabricated slurry: add 8 parts of deionized water to the first container in parts by weight, add 1.2 parts of dispersant, 0.5 parts of defoamer and 2 parts of film-forming agent in a disperser at 300 rpm, and stir and disperse for 5 minutes; add 15 parts of pigment and filler, stir and disperse for 3 minutes; add 8 parts of composite wear-resistant filler, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of a grinder at 3000 rpm, and grind for 2 hours to obtain a prefabricated slurry;

[0047] Preparation of viscous liquid: Add 35 parts of resin emulsion to the second container, add the prefabricated slurry on the disperser at a speed of 300 rpm, adjust the disperser speed to 800 rpm, stir and disperse for 3 minutes, add 0.2 parts of anti-scratch agent, 0.3 parts of wetting agent and 0.5 parts of thickener, and adjust the viscosity of the mixed liquid to between 75 and 85 KU to obtain a viscous liquid;

[0048] Purification treatment: Filter with a 100-mesh silk bag to remove impurities in the viscous liquid to obtain component A, and package and seal component A for later use.

[0049] 2) Preparation steps of component B:

[0050] In parts by weight, 70 parts of aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to the third container, and the two are stirred and dispersed uniformly to obtain component B;

[0051] 3) By weight, component A and component B are mixed evenly at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

[0052] Among them, the composite wear-resistant filler includes 6 parts of ultrafine ceramic microspheres and 2 parts of polytetrafluoroethylene wax powder, the resin emulsion uses polyhydroxy acrylic resin, the color filler uses 7.5 parts of titanium dioxide, 0.5 parts of attapulgite and 7 parts of ultrafine talc, the film-forming agent uses 1 part of propylene glycol butyl ether and 1 part of AMP-95 (2-amino-2-methyl-1-propanol), the dispersant uses polymers and surfactants containing high-efficiency pigment adsorption groups, the defoaming agent uses polymer composite mineral oil, the anti-scratch agent uses modified hydroxyl functional polydimethylsiloxane solution, the wetting agent uses silicone twin structure surfactant, and the thickener uses alkali-swellable acrylic resin.

[0053] Embodiment 3:

[0054] The embodiment of the present invention provides a wear-resistant and anti-corrosion coating, which comprises, by weight:

[0055] Raw materials of component A: 55 parts of resin emulsion, 20 parts of composite wear-resistant filler, 10 parts of pigment filler, 5 parts of film-forming agent and auxiliary agents; the auxiliary agents include 0.5 parts of defoaming agent, 0.6 parts of dispersant, 0.3 parts of anti-scratch agent, 0.8 parts of wetting agent and 0.3 parts of thickener.

[0056] Raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

[0057] The preparation method of the wear-resistant and anti-corrosion coating comprises:

[0058] 1) Preparation steps of component A:

[0059] Prefabricated slurry: add 10.8 parts of deionized water to the first container in parts by weight, add 0.6 parts of dispersant, 0.5 parts of defoamer and 5 parts of film-forming agent in a disperser at 300 rpm, and stir and disperse for 8 minutes; add 10 parts of pigment and filler, stir and disperse for 5 minutes; add 20 parts of composite wear-resistant filler, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of a grinder and grind at 3000 rpm for 2 hours to obtain a prefabricated slurry;

[0060] Preparation of viscous liquid: Add 55 parts of resin emulsion to the second container, add the prefabricated slurry on the disperser at a speed of 300 rpm, adjust the disperser speed to 500 rpm, stir and disperse for 4 minutes, add 0.3 parts of anti-scratch agent, 0.8 parts of wetting agent and 0.3 parts of thickener, and adjust the viscosity of the mixed liquid to between 75 and 85 KU to obtain a viscous liquid;

[0061] Purification treatment: Filter with a 100-mesh silk bag to remove impurities in the viscous liquid to obtain component A, and package and seal component A for later use.

[0062] 2) Preparation steps of component B:

[0063] In parts by weight, 70 parts of aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to the third container, and the two are stirred and dispersed uniformly to obtain component B;

[0064] 3) By weight, component A and component B are mixed evenly at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

[0065] Among them, the composite wear-resistant filler includes 12 parts of ultrafine ceramic microspheres and 8 parts of alumina, the resin emulsion adopts high-functionality polyurethane resin, the color filler adopts 5.5 parts of titanium dioxide, 0.5 parts of attapulgite and 4 parts of ultrafine wollastonite, the film-forming agent adopts 2.5 parts of propylene glycol butyl ether and 2.5 parts of diethylene glycol dimethyl ether, the dispersant adopts acrylic block polymer, the defoaming agent adopts polyether siloxane copolymer emulsion, the anti-scratch agent adopts modified hydroxyl-functional polydimethylsiloxane solution, the wetting agent adopts silicone twin structure surfactant, and the thickener adopts alkali-swellable acrylic resin.

[0066] Embodiment 4:

[0067] The embodiment of the present invention provides a wear-resistant and anti-corrosion coating, which comprises, by weight:

[0068] Raw materials of component A: 47 parts of resin emulsion, 26 parts of composite wear-resistant filler, 8 parts of pigment filler, 2 parts of film-forming agent and auxiliary agents; the auxiliary agents include 0.6 parts of defoaming agent, 0.6 parts of dispersant, 0.3 parts of anti-scratch agent, 0.5 parts of wetting agent and 0.6 parts of thickener.

[0069] Raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

[0070] The preparation method of the wear-resistant and anti-corrosion coating comprises:

[0071] 1) Preparation steps of component A:

[0072] Prefabricated slurry: add 14.8 parts of deionized water to the first container in parts by weight, add 0.6 parts of dispersant, 0.6 parts of defoamer and 2 parts of film-forming agent in a disperser at a speed of 300 rpm, and stir and disperse for 5 minutes; add 8 parts of pigment and filler, stir and disperse for 3 minutes; add 26 parts of composite wear-resistant filler, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of a grinder at a speed of 3000 rpm, and grind for 2 hours to obtain a prefabricated slurry;

[0073] Preparation of viscous liquid: Add 47 parts of resin emulsion to the second container, add the prefabricated slurry on the disperser at a speed of 300 rpm, adjust the disperser speed to 500 rpm, stir and disperse for 5 minutes, add 0.3 parts of anti-scratch agent, 0.5 parts of wetting agent and 0.6 parts of thickener, and adjust the viscosity of the mixed liquid to between 75 and 85 KU to obtain a viscous liquid;

[0074] Purification treatment: Filter with a 100-mesh silk bag to remove impurities in the viscous liquid to obtain component A, and package and seal component A for later use.

[0075] 2) Preparation steps of component B:

[0076] In parts by weight, 70 parts of aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to the third container, and the two are stirred and dispersed uniformly to obtain component B;

[0077] 3) By weight, component A and component B are mixed evenly at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

[0078] Among them, the composite wear-resistant filler includes 9 parts of ultrafine ceramic microspheres, 9 parts of alumina and 8 parts of polytetrafluoroethylene wax powder, the resin emulsion uses fluorocarbon resin, the color filler uses 7.5 parts of titanium dioxide and 0.5 parts of attapulgite, the film-forming agent uses 1 part of dipropylene glycol butyl ether and 1 part of diethylene glycol dimethyl ether, the dispersant uses acrylic block polymer, the defoaming agent uses polyether modified silicone containing silicon dioxide, the anti-scratch agent uses modified hydroxyl functional polydimethylsiloxane solution, the wetting agent uses silicone twin structure surfactant, and the thickener uses alkali swellable acrylic resin.

[0079] Embodiment 5:

[0080] The embodiment of the present invention provides a wear-resistant and anti-corrosion coating, which comprises, by weight:

[0081] Raw materials of component A: 35 parts of resin emulsion, 20 parts of composite wear-resistant filler, 10 parts of pigment filler, 2 parts of film-forming agent and auxiliary agents; the auxiliary agents include 1.2 parts of defoaming agent, 1.2 parts of dispersant, 0.3 parts of anti-scratch agent, 0.1 parts of wetting agent and 1 part of thickener.

[0082] Raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

[0083] The preparation method of the wear-resistant and anti-corrosion coating comprises:

[0084] 1) Preparation steps of component A:

[0085] Prefabricated slurry: add 16 parts of deionized water into the first container in parts by weight, add 1.2 parts of dispersant, 1.2 parts of defoamer and 2 parts of film-forming agent in a disperser at a speed of 300 rpm, and stir and disperse for 5 minutes; add 10 parts of pigment and filler, stir and disperse for 3 minutes; add 20 parts of composite wear-resistant filler, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of a grinder at a speed of 3000 rpm, and grind for 2 hours to obtain a prefabricated slurry;

[0086] Prepare a viscous liquid: add 35 parts of the resin emulsion to the second container, add the prefabricated slurry on a disperser at a speed of 300 rpm, adjust the disperser speed to 500 rpm, stir and disperse for 5 minutes, add 0.3 parts of an anti-scratch agent, 0.1 parts of a wetting agent and 1 part of a thickener, and adjust the viscosity of the mixed liquid to between 75 and 85 KU to obtain a viscous liquid;

[0087] Purification treatment: Filter with a 100-mesh silk bag to remove impurities in the viscous liquid to obtain component A, and package and seal component A for later use.

[0088] 2) Preparation steps of component B:

[0089] In parts by weight, 70 parts of aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to the third container, and the two are stirred and dispersed uniformly to obtain component B;

[0090] 3) By weight, component A and component B are mixed evenly at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

[0091] Among them, the composite wear-resistant filler includes 14 parts of aluminum oxide and 6 parts of polytetrafluoroethylene wax powder, the resin emulsion adopts polyhydroxy acrylic resin, the color filler adopts 9.5 parts of titanium dioxide and 0.5 parts of attapulgite, the film-forming agent adopts 1 part of diethylene glycol dimethyl ether and 1 part of AMP-95 (2-amino-2-methyl-1-propanol), the dispersant adopts polymers and surfactants containing high-efficiency pigment adsorption groups, the defoaming agent adopts polyether siloxane copolymer emulsion, the anti-scratch agent adopts modified hydroxyl functional polydimethylsiloxane solution, the wetting agent adopts silicone twin structure surfactant, and the thickener adopts alkali swellable acrylic resin.

[0092] Comparative Example:

[0093] This embodiment is a comparative embodiment. The coating of this embodiment includes, by weight:

[0094] Raw materials of component A: 50 parts of resin emulsion, 15 parts of composite wear-resistant filler, 15 parts of pigment filler, 2.5 parts of film-forming agent and auxiliary agents; the auxiliary agents include 0.7 parts of defoaming agent, 0.6 parts of dispersant, 0.5 parts of anti-scratch agent, 0.3 parts of wetting agent and 0.4 parts of thickener.

[0095] Raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

[0096] The preparation method of the wear-resistant and anti-corrosion coating comprises:

[0097] 1) Preparation steps of component A:

[0098] Prefabricated slurry: Add 15 parts of deionized water by weight into the first container in sequence, add 0.6 parts of dispersant, 0.7 parts of defoaming agent and 2.5 parts of film-forming agent in the disperser at 300 rpm, and stir and disperse for 5 minutes; add 15 parts of color filler, stir and disperse for 3 minutes; add 15 parts of composite wear-resistant filler, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of the grinder and grind at 3000 rpm for 2 hours to obtain a prefabricated slurry.

[0099] Preparation of viscous liquid: Add 50 parts of resin emulsion to the second container, add the prefabricated slurry on the disperser at a speed of 300 rpm, adjust the disperser speed to 500 rpm, stir and disperse for 5 minutes, add 0.5 parts of anti-scratch agent, 0.3 parts of wetting agent and 0.4 parts of thickener, and adjust the viscosity of the mixed liquid to between 75 and 85 KU to obtain a viscous liquid;

[0100] Purification treatment: Filter with a 100-mesh silk bag to remove impurities in the viscous liquid to obtain component A, and package and seal component A for later use.

[0101] 2) Preparation steps of component B:

[0102] In parts by weight, 70 parts of aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to the third container, and the two are stirred and dispersed uniformly to obtain component B;

[0103] 3) By weight, component A and component B are mixed evenly at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

[0104] Among them, the composite wear-resistant filler in this embodiment is precipitated barium sulfate, the resin emulsion is high-functional polyurethane resin, the color filler is 14.5 parts of titanium dioxide and 0.5 parts of attapulgite, the film-forming agent is 1.5 parts of propylene glycol butyl ether and 1 part of dipropylene glycol butyl ether, the dispersant is maleic acid copolymer sodium salt, the defoaming agent is polyether siloxane copolymer emulsion, the anti-scratch agent is modified hydroxyl functional polydimethylsiloxane solution, the wetting agent is silicone twin structure surfactant, and the thickener is alkali swellable acrylic resin.

[0105] It should be noted that the particle size range of the ultrafine wollastonite and ultrafine talc in the above embodiment is 1-10 μm, and the particle size range of the ultrafine ceramic microsphere is 1-5 μm. According to actual applications, those skilled in the art may also select zirconium oxide as the composite wear-resistant filler. In addition, in the above embodiments, the polymer and surfactant containing high-efficiency pigment adsorption groups are selected from Evonik's TEGO760W wetting dispersant, the acrylic block polymer is selected from BYK's BYK190 dispersant, the sodium salt of maleic acid copolymer is selected from BASF's DISPEX CX 4320AM dispersant, the polyether siloxane copolymer emulsion is selected from BYK's BYK-024 defoamer, the polyether modified silicone containing silicon dioxide is selected from Evonik's TEGO902W defoamer, the polymer composite mineral oil is BASF's FOAMSTAR ST2437 defoamer, the modified hydroxyl-functional polydimethylsiloxane solution is selected from BYK's BYK-SILCLEAN3720 anti-scratch agent, the silicone twin structure surfactant is selected from Evonik's TEGO4100, and the alkali-swellable acrylic resin is selected from Goteborg's XS-83 thickener.

[0106] The coatings prepared in the above Examples 1-6 were prepared into samples for performance testing. Among them, the abrasion sample was sprayed with a film thickness of 40±3um, and was tested using a Taber abrasion tester, with a grinding wheel model of CS-17 and a rotation speed of 60r / min. The wear resistance was tested according to the GB / T1768-2006 standard "Determination of Wear Resistance of Paints and Varnishes by Rotating Rubber Grinding Wheel Method"; the water resistance was tested according to the GB / T1733-1993 immersion method, the hardness was tested according to the GB / T 6739-2006 standard, and the adhesion was tested according to the GB / T9286-1998 standard by the cross-cut method; the flexibility was tested according to the GB / T 1731-2020 standard by bending a 2mm diameter shaft rod; the impact resistance was tested according to the GB / T 1732-1993 standard with a 1kg hammer punching 50cm. The test performance results of the embodiment are detailed in Table 1.

[0107] Table 1

[0108]

[0109] Table 1 is a comparison table of the performance test results between Examples 1-5 and the comparative examples. Three wear specimens were used for each group to take the average value. By comparison, it can be concluded that the wear mass of the coating of Examples 1-5 at 1000r / 1000g is much smaller than that of the coating of the comparative example.

[0110] Figures 1 to 5 The pictures of the sample wear results of Examples 1-5 are respectively, Figure 6 The following is a picture of the sample wear results of the comparative example. By visual observation, compared with the surface wear marks of the samples of Examples 1-3, the surface wear marks of the samples of Examples 4-5 at the ring position are relatively slight and not obvious, while the surface wear marks of the samples of the comparative example at the ring position are obvious. Therefore, the wear resistance and scratch resistance of the samples of Examples 4 and 5 are better in comparison. In addition, the water resistance and impact resistance of Examples 4 and 5 are better than those of Examples 1-3 and the comparative example.

[0111] The composite wear-resistant fillers in the wear-resistant and anti-corrosion coatings of the embodiments of the present invention all use polytetrafluoroethylene wax powder. Generally, the dispersibility of polytetrafluoroethylene wax powder in water-based coating systems is poor and unstable. Therefore, the use of a dispersant with a high-efficiency pigment adsorption group can enhance the dispersion stability of polytetrafluoroethylene wax powder in water-based coating systems and reduce the occurrence of agglomeration, thereby enabling the wear-resistant and anti-corrosion coating to form a uniform paint film surface after spraying. The polytetrafluoroethylene wax powder and dispersant form a surface protection layer together with the anti-scratch agent to compensate for the wear resistance of the resin component in the coating and improve the overall wear resistance of the coating. It can be understood that the synergistic effect between the polytetrafluoroethylene wax powder, dispersant and anti-scratch agent in the wear-resistant and anti-corrosion coating of the present invention enhances the wear resistance of the wear-resistant and anti-corrosion coating and provides the first line of protection for the coating after coating.

[0112] In addition, ultrafine ceramic microspheres are used in the wear-resistant and anti-corrosion coatings of Examples 1-4. Among them, the wear-resistant particles used in the composite wear-resistant filler are usually irregular particles, and the use of ultrafine ceramic microspheres can be evenly dispersed among other wear-resistant particles. It can be understood that ultrafine ceramic microspheres have different levels of particle sizes from other wear-resistant materials. During the dispersion process, smaller spherical ceramic particles can be evenly dispersed among larger wear-resistant particles, thereby making the coating denser and the structure more stable, further enhancing the wear resistance of the wear-resistant and anti-corrosion coating. Among them, the wear-resistant particles include ceramic particles such as aluminum oxide, silicon carbide and zirconium oxide.

[0113] That is, under the coverage of the surface wear-resistant coating, some of the ultrafine ceramic microspheres in the coating are evenly mixed and dispersed between the wear-resistant particles, providing a second line of protection for the coated coating, while cooperating with the high cross-linking density three-dimensional network structure formed by the reaction of the two components.

[0114] In summary, compared with the current topcoat coatings, the wear loss of the wear-resistant and anti-corrosion coating of the present invention is reduced by up to about 85.2% compared with the current products. It is suitable for the service environment of power equipment in windy and sandy environments to reduce the erosion rate of wind and sand on the coating, extend the service life of the equipment, and significantly improve the wear resistance and protection performance of power equipment in the northwest windy and sandy areas, which helps to improve the problem of wind and sand abrasion of the surface coating of power equipment.

[0115] Secondly, compared with existing anti-corrosion coatings, the wear-resistant anti-corrosion coating of the present invention is prepared using water as a solvent, which significantly reduces the emission of volatile organic compounds in solvent-based coatings and improves the environmental performance of the wear-resistant anti-corrosion coating.

[0116] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.

Claims

1. A wear-resistant and anti-corrosion coating, characterized in that: By weight, the coating comprises: Raw materials of component A: 35-55 parts of resin emulsion, 8-26 parts of composite wear-resistant filler, 8-15 parts of pigment filler, 2-5 parts of film-forming agent and 1.5-3 parts of auxiliary agent; and Raw materials of component B: 70 parts of aliphatic isocyanate trimer and 30 parts of propylene glycol diacetate.

2. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The resin emulsion includes at least one of a high-functionality polyurethane resin, a fluorocarbon resin and a polyhydroxy acrylic resin.

3. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The composite wear-resistant filler comprises at least one of ultrafine ceramic microspheres, aluminum oxide, silicon carbide, polytetrafluoroethylene wax powder and zirconium oxide.

4. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The pigment and filler comprises at least one of titanium dioxide, attapulgite, precipitated barium sulfate, ultrafine wollastonite and ultrafine talc.

5. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The film-forming agent includes at least one of alcohol ester dodecanedione, propylene glycol butyl ether, AMP-95, dipropylene glycol butyl ether and diethylene glycol dimethyl ether.

6. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The auxiliary agent includes 0.5 to 1.2 parts of a defoaming agent, 0.5 to 1.2 parts of a dispersant, 0.1 to 0.8 parts of an anti-scratch agent, 0.1 to 0.8 parts of a wetting agent and 0.3 to 1 parts of a thickener.

7. The wear-resistant and anti-corrosion coating according to claim 6, characterized in that: The dispersant at least comprises a polymer containing a high-efficiency pigment adsorption group and a surfactant, a sodium salt of a maleic acid copolymer, and an acrylic acid block polymer.

8. The wear-resistant and anti-corrosion coating according to claim 6, characterized in that: The defoaming agent comprises at least one of polyether siloxane copolymer emulsion, polyether modified silicone containing silicon dioxide and polymer composite mineral oil.

9. The wear-resistant and anti-corrosion coating according to claim 6, characterized in that: The anti-scratch agent comprises a modified hydroxyl functional polydimethylsiloxane solution, the wetting agent comprises an organic silicon twin structure surfactant, and the thickener comprises an alkali swelling acrylic resin.

10. A method for preparing the wear-resistant and anti-corrosion coating according to any one of claims 1 to 9, characterized in that: include: Preparation steps of component A: Prefabricated slurry: add 8 to 16 parts of deionized water into the first container in parts by weight, add 0.5 to 1.2 parts of dispersant, 0.5 to 1.2 parts of defoamer, and 2 to 5 parts of film-forming agent in a disperser at a speed of 300 to 500 rpm, and stir and disperse for 5 to 8 minutes; add 8 to 15 parts of pigments and fillers, stir and disperse for 3 to 5 minutes; add 8 to 26 parts of composite wear-resistant fillers, stir and disperse for 10 minutes to obtain a stirred and dispersed material, put the stirred and dispersed material into the tank of a grinder, grind at a speed of 3000 rpm for 2 to 3 hours to obtain a prefabricated slurry; Prepare a viscous liquid: add 35-55 parts of the resin emulsion to the second container, add the prefabricated slurry on a disperser at a speed of 300 rpm, adjust the speed of the disperser to 500-800 rpm, stir and disperse for 3-5 minutes, add 0.1-0.8 parts of an anti-scratch agent, 0.1-0.8 parts of a wetting agent and 0.3-1 parts of a thickener, and adjust the viscosity of the mixed liquid to between 75 and 85 KU to obtain a viscous liquid; Purification treatment: filtering with a 100-mesh silk bag to remove impurities in the viscous liquid to obtain the A component; Preparation steps of component B: In parts by weight, 70 parts of aliphatic isocyanate trimer as a curing agent and 30 parts of propylene glycol diacetate as a solvent are added to the third container, and the two are stirred and dispersed uniformly to obtain the B component; In parts by weight, the component A and the component B are evenly mixed at a ratio of 4.5:1 to obtain a wear-resistant and anti-corrosion coating.

Citation Information

Cited By

  • Water-based two-component low-temperature stoving varnish for photovoltaic frame and preparation method of water-based two-component low-temperature stoving varnish

    CN121950155A